The Effect of Learning Habits and Learning Motivation on The Learning Achievement of The Workshop Theory in Aviation Politechnic Surabaya - Jamaludin, Jamaludin; Eko, Hariadi; Arie, Wardhono (International Journal for Educational and Vocational Studies, 2020)
This study was conducted to determine the Effect of Learning Habits and Learning Motivation on the Learning Achievements in Workshop Theory for Diploma III Aircraft Engineering Students in Aviation Politechnic Surabaya 2018/2019. The Effect of Study Habits and Learning Motivation together in Workshop Theory for Diploma III Aircraft Engineering Students in Aviation Politechnic Surabaya 2018/2019. This research includes Ex-post Facto with a quantitative approach. The population in this study were 48 students of Diploma III Aircraft Engineering in Aviation Politechnic Surabaya 2018/2019. Data collection techniques are done through documentation and questionnaires. Documentation is used to obtain data on the number of students and Workshop Theory Learning Achievement data, while the questionnaire is used to collect data on Learning Habits and Learning Motivation variables that have been tested for validity and reliability. Data analysis techniques used simple regression analysis and multiple predictor regression analysis. Before conducting the hypothesis test, the analysis prerequisite test is linearity test and multicollinearity test. Simple regression analysis is used to test the first and second hypotheses, while the double regression analysis of two predictors is used to test the third hypothesis. The results of this study are that there is a positive influence on Study Habits and Learning Motivation on Learning Achievements in Workshop Theory for Students of Diploma III Aircraft Engineering in Aviation Politechnic Surabaya 2018/2019, proven by the results of testing the study habits and learning motivation variables that have a t-value of 0,000. With a t-value below 0.050, the variables of study habits and learning motivation are very significant influences on learning achievement.